Організаційно-правові засади діяльності Державного бюро розслідувань у системі правоохоронних органів України - Гусаров, С. М.; Gusarov, S. M.; Лісойван, Я. М.; Lisoivan, Ya. M.; Сергій Гусаров (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 2 (97). – С. 142-150, 2022)
Проаналізовано місце та роль Державного бюро розслідувань у сучасній класифікаційній системі правоохоронних органів України. Встановлено сутність дефініції «правоохоронні органи», проаналізовано особливості їх діяльності. Наголошено, що для визначення належності того чи іншого державного органу до категорії правоохоронного, йому повинні бути притаманні певні специфічні ознаки. Констатовано, що, незважаючи на короткий строк діяльності, Державне бюро розслідувань за всіма вищевказаними ознаками є належним до правоохоронних органів України. Проаналізовано повноваження та функції Державного бюро розслідувань і встановлено організаційно-правові засади його діяльності.

The place and role of the State Bureau of Investigation in the modern classification system of law enforcement agencies of Ukraine is analyzed. The essence of the definition of “law enforcement agencies” is established, and the peculiarities of their activities are analyzed. It has been noted that modern law enforcement bodies must be considered as state bodies that function in the general system of public authorities and perform, in accordance with current legislation, relevant functions in various fields of internal and external activity of the state, the purpose of which is to observe and implement the rights and freedoms of citizens, legality and law and order with compliance with the rules and procedures regulated by law within the limits of their competence. It has been emphasized that in order to determine whether a state body belongs to the category of law enforcement, it must have certain specific characteristics. The following signs are the state and authority nature of the activity; the right to apply measures of state coercion; execution of special powers to implement the law enforcement function of the state on a professional basis; special material, technical and personnel support of activities; statutory nature of activity; enforceable nature of law enforcement agency decisions, and more. It has been established that, despite the short period of activity, the State Bureau of Investigations belongs to the law enforcement agencies of Ukraine by all the above-mentioned features. The powers and functions of the State Bureau of Investigation are analyzed. It has been emphasized that the main ones are solving the tasks of prevention, detection, termination, disclosure and investigation of crimes committed by officials who occupy a particularly responsible position; crimes committed by NABU officials, the Deputy Prosecutor General - head of the Specialized Anti-Corruption Prosecutor's Office or other prosecutors of the Specialized Anti-Corruption Prosecutor's Office; crimes against the established order of military service.

Проанализированы место и роль Государственного бюро расследований в современной классификационной системе правоохранительных органов Украины. Установлена ​​сущность дефиниции «правоохранительных органов», проанализированы особенности их деятельности. Отмечено, что для определения принадлежности того или иного государственного органа к категории правоохранительного ему должны быть присущи определенные специфические признаки. Констатировано, что, несмотря на короткий срок деятельности, Государственное бюро расследований по всем вышеуказанным признакам относится к правоохранительным органам Украины. Проанализированы полномочия и функции Государственного бюро расследований и установлены организационно-правовые основы его деятельности.
Organizational and legal principles of the State Bureau of Investigation activity in the system of law enforcement agencies of Ukraine
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Державне бюро розслідувань; правоохоронні органи; повноваження; функції; державні органи; правові засади; State Bureau of Investigation; law enforcement agencies; powers; functions; state bodies; legal principles; Государственное бюро расследований; правоохранительные органы; полномочия